Critical-Care Pain Observation Tool (CPOT) and Wong-Baker Faces Pain Rating Scale in Measuring Pain Level of Patient With Mechanical Ventilation - Arsyawina Arsyawina; Mardiyono Mardiyono; Sarkum Sarkum (Jurnal Riset Kesehatan, 2014)
Assesing pain in mechanically ventilated patients is a great challenge. Mechanical ventilated patients are often unable to self-report the presence of pain. CPOT is a behavioral pain scale which has been developed and validated for measuring pain in nonverbal critically ill adults. Purpose: This study was to compare CPOT and Wong-Baker by examining psychometric properties including reliability, validity and responsiveness. Method : A repeated measures design was chosen for this quantitative study with 31 samples of mechanically ventilated patients. Result : The ICC values of inter-rater reliability were high at 0,965 for CPOT and low at 0,423 for Wong-Baker. Validity was demonstrated by the change in CPOT and Wong-Baker, which were significantly higher during painful procedures,with averages for CPOT 1,32 – 1,42 at rest and 2,39-4,26 during procedure (p less than 0,001) and for Wong-Baker 4,52 – 4,65 at rest and 5,29-5,74 during procedure. The CPOT exhibited excellent responsiveness, with an effect size ranging from 5,0 to 5,4 better then Wong-Baker with an effect size ranging from 0,8 to 2,2. Conclusion : This study demonstrated that the CPOT can be valid, reliabeland more responsiveness for measuring pain in mechanical ventilated patients.